Abortion Dispensation Due to Verified Contraceptive Failure: A Normative Juridical Study of Article 60 of Law Number 17 of 2023 on Health - I Made Oka Widiabdi Husada; Sirajuddin Sirajuddin; Heri Sugeng Widodo; Erics Efrany (Eduvest - Journal of Universal Studies, 2026)
Indonesia faces a paradox in its reproductive health policy: while actively promotes the Family Planning program but explicitly acknowledges the possibility of contraceptive failure under Law Number 52 of 2009. It fails to provide a legal remedy when such failure results in unintended pregnancy. Law Number 17 of 2023 on Health and Number 1 of 2023 on the Criminal Code (KUHP) permit abortion only under limited exceptions. Namely, medical emergencies and pregnancies among rape victims, without accommodating contraceptive failure, notwithstanding the State’s recognition that such failures may occur. This study aims to (1) analyze the legal standing of unintended pregnancy resulting from verified contraceptive failure within the framework of exceptions to the prohibition of abortion and (2) develop a contextually legal dispensation model for abortion in such cases within the Indonesian legal system. The research employs a normative legal method, utilizing conceptual, statutory and comparative approaches. Secondary legal materials are examined through systematic, teleological and extensive interpretation, alongside a comparative analysis of six selected countries. The findings demonstrated that the legal status of contraceptive failure is characterized by a condition of normative incompleteness (onvolledigheid van de norm), thereby undermining the principles of legal certainty and protection. Interpretation of “medical emergency” grounded in the World Health Organization’s definition of health, may serve as an entry point to accommodate such cases. The appropriate legal construction lies in the establishment of a dispensation mechanism, implemented through an integrated dispensation panel at the district/city level.